IMPLEMENTASI PENGEMBANGAN SILABUS BERBASIS KOMPETENSI DI SEKOLAH DASAR NEGERI 01 KELAPA GADING TIMUR - Jannah, Miftahul; Ulfah, Maria (Journal Education and Government Wiyata, 2024)
This research aims to describe the implementation of caompetency-based syllabusdevelopment at SDN 01 Kelapa Gading Timur. This research uses a qualitativemethod with a descriptive approach. Data collection was carried throughobservation, interviews and documentation studies. The research results show thatthe implementation of competency-based at SDN 01 Kelapa Gading Timurincludes planning. Impementation and evaluation stages. In the planning stage theteacher prepares the syllabus according to competencies. At the implementationstage, the teacher uses the syllabus as a reference in preparing learningimplementation plans and carrying out kearning activities. The evaluation stage iscarried out to assess the suitability between the syllabus and the implementationof learning. Thus, it can be concluded that the implementation of competencybased at SDN 01 Kelapa Gading Timur has been carried out well.